Szkoła jako przestrzeń inkubacji aktywności cyfrowej nauczycieli edukacji wczesnoszkolnej - Natalia Walter (Problemy Wczesnej Edukacji)
In the paper we argue that school is a space for growing and developing digital activity of early education teachers. Based on an observational study and a literature review, we identified factors affecting such activity, i.e., individual features of teachers (competences, motivation, attitude towards self-development, lowliness, and willingness for change), their competence in handling electronic devices, technical equipment available at school, support from the school community along with clearly stated expectations (that the use of digital media is a must, not an option) and availability of trainings and places for exchanging experience and good practices.